2018
DOI: 10.1093/cercor/bhx347
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Anodal Transcranial Direct Current Stimulation Over the Ventrolateral Prefrontal Cortex on Episodic Memory Formation and Retrieval

Abstract: In the past decade, several studies have investigated the effects of transcranial direct current stimulation (tDCS) on episodic memory abilities. However, the specific conditions under which tDCS affects memory remain largely unclear. Here, we report data from 4 experiments aimed at investigating the effects of anodal tDCS over the left ventrolateral prefrontal cortex (VLPFC) on verbal episodic memory. We evaluated tDCS-induced effects as a function of time of administration, nature of the memory encoding task… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
58
0
5

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 43 publications
(64 citation statements)
references
References 63 publications
1
58
0
5
Order By: Relevance
“…These results suggest that tDCS modulation of memory encoding may also affect the balance of detail and gist in these memories, depending on the polarity of stimulation, and largely depends on ongoing encoding strategies. A study examining the effects of anodal tDCS to the left VLPFC found that intentional, but not incidental, encoding of verbal material was improved from stimulation, but this effect was only observed when stimulation was applied concurrently with encoding and not when stimulation was applied immediately before encoding (Medvedeva et al, 2018). This study also included a sample of older adults and found that they too benefited from concurrent stimulation during intentional memory encoding.…”
Section: Discussionmentioning
confidence: 83%
See 1 more Smart Citation
“…These results suggest that tDCS modulation of memory encoding may also affect the balance of detail and gist in these memories, depending on the polarity of stimulation, and largely depends on ongoing encoding strategies. A study examining the effects of anodal tDCS to the left VLPFC found that intentional, but not incidental, encoding of verbal material was improved from stimulation, but this effect was only observed when stimulation was applied concurrently with encoding and not when stimulation was applied immediately before encoding (Medvedeva et al, 2018). This study also included a sample of older adults and found that they too benefited from concurrent stimulation during intentional memory encoding.…”
Section: Discussionmentioning
confidence: 83%
“…Another study found that anodal tDCS to the left DLPFC during retrieval improved metacognitive monitoring accuracy for semantic knowledge questions while actually trending toward worse recall performance in another study (Chua & Ahmed, 2016). Furthermore, a study examining anodal tDCS to the left VLPFC did not show any benefits from stimulation immediately before or concurrently during retrieval of verbal material (Medvedeva et al, 2018). Considering that prefrontal tDCS administered during post-encoding consolidation of retrieval has not led to consistent mnemonic improvements, what mechanisms could make stimulation of a spatially proximate region like RLPFC able to yield the improvements in source memory retrieval demonstrated in the present study?…”
Section: Discussionmentioning
confidence: 98%
“…Only a handful of studies investigated the effects of tDCS on episodic memory encoding in healthy elderly subjects: anodal tDCS applied over the right temporoparietal cortex during memory encoding significantly improved delayed recall performance on an associative objectlocation learning task (Flöel et al, 2012). Another study applying anodal tDCS over the left VLPFC during word learning resulted in increased discrimination accuracy in a recognition task (Medvedeva et al, 2019). Anodal tDCS applied over the left dorsolateral PFC (DLPFC) during the encoding of a list of words resulted in enhanced performance on a free recall task (Sandrini et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…whereby the left VLPFC is responsible for declarative memory encoding and the left DLPFC is responsible for subsequent organisation and retrieval processes (Blumenfeld, Lee, & D'Esposito, 2014;Galli, Feurra, Pavone, Sirota, & Rossi, 2017;Medvedeva et al, 2018;for reviews, see Blumenfeld & Ranganath, 2007;Fletcher & Henson, 2001;Nyhus & Badre, 2015). Notably, the VLPFC and the DLPFC are thought to coordinate their activity via neural oscillations (Nyhus & Badre, 2015).…”
Section: Resultsmentioning
confidence: 99%